Cardiovascular toxicity of abacavir: a clinical controversy in need of a pharmacological explanation. (24th August 2017) - Alvarez, Angeles; Orden, Samuel; Andújar, Isabel; Collado-Diaz, Victor; Núñez-Delgado, Sara; Galindo, Maria J.; Estrada, Vicente; Apostolova, Nadezda; Esplugues, Juan V.
Abstract : N/A: There is a long-lasting controversy surrounding an association between abacavir (ABC) and an increased risk of cardiovascular disease in HIV-positive patients. Although differing in their specifics, a number of published cohort studies and clinical trials support such an association, usually relating it to recent exposure to the drug, independently of traditional predisposing factors. However, other clinical trials have failed to reveal such a relation and have pointed to methodological differences to explain discrepancies. Significantly, the controversy has been fueled by the lack of a credible mechanism of action to justify the putative detrimental actions of ABC. There is a myriad of contradictory clinical indicators which are not clearly compatible with known profiles of either vascular physiopathology or pharmacological interference. However, basic research has recently hinted at altered homeostatic mechanisms, though this requires clinical validation. In particular, recurrent evidence – both clinical and experimental – relates ABC with vascular inflammation, a leading contributor to the atherosclerotic plaque and thrombosis. ABC's chemical structure is very close to that of endogenous purines (ATP, ADP and AMP), major paracrine signaling molecules capable of triggering prothrombotic and proinflammatory vascular programs. Other proposed mechanisms are a competitive inhibition of guanylyl cyclase in platelets and a subsequent decrease in cyclic guanosine monophosphate (cGMP). The present review aims to shed light on this complex subject by summarizing and critically evaluating all the available clinical data regarding a relationship between ABC and cardiovascular disease, and to put forward potential pharmacological explanations compatible with both the clinical scenario and experimental findings.